Are first year medical students ready for OSCE? - Sim, Joong Hiong; Vijayananthan, Anushya; Abdul Aziz, Yang Faridah; Mansor, Azura; Ahmad Tajuddin, Nur Amani; Idris, Norisma; Jaafar, Zulkarnain; Omar, Asma (Japan International Cultural Exchange Foundation, 2018)
Objective: This study aimed to assess First Year medical students' readiness for OSCE. Design: This is a retrospective study where secondary data comprising both quantitative and qualitative data, were analysed. Materials and Methods: Three cohorts of First Year medical students (n = 454) took a 5-station OSCE. Two categories of tasks were assessed. Category A assessed patient and doctor interaction while Category B assessed clinical skills. A student must be scored as satisfactory in at least four out of five stations for a pass in Category A and at least three out of five stations for a pass in Category B. A pass in both Categories A and B is required to pass the OSCE. For each cohort, overall passing percentage, as well as passing percentage for Category A and Category B of each station, was computed. Examiners' feedback on students' performance during OSCE for each station was examined. Feedback from students regarding the OSCE was also sought. Results: For Cohort 2013, Cohort 2014 and Cohort 2015, 174/179 (97.21%), 118/129 (91.47%) and 140/147 (95.24%) of students passed the OSCE respectively. Cohort 2013, Cohort 2014 and Cohort 2015 recorded mean percent pass of (95.31%, 88.83%), (89.15%, 83.10%) and (98.36%, 84.52%) for Category A and Category B respectively. Examiners' feedback was generally favourable. Feedback from students was mixed but constructive and generally encouraging. Conclusions: Based on students' performance in the OSCE as well as feedback from both examiners and students, First Year medical students appeared to be ready for OSCE assessment.